2020
DOI: 10.1159/000512079
|View full text |Cite
|
Sign up to set email alerts
|

Change in Allergy Practice during the COVID-19 Pandemic

Abstract: <b><i>Background:</i></b> International guidelines in asthma and allergy has been updated for COVID-19 pandemic and pandemic has caused dramatic changes in allergy and immunology services. However, it is not known whether specialty-specific recommendations for COVID-19 are followed by allergists. <b><i>Objectives:</i></b> By conducting this study, we aimed to determine the attitudes and experiences of adult/pediatric allergists on allergy management during COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 7 publications
1
32
0
Order By: Relevance
“…This also relates to the changes in treatment linked to the pandemic. A recent study performed among allergists, for example, reported that one third of participating physicians stopped systemic steroid treatment in their patients with asthma 35 . Another study performed among rheumatologists found that one third of participating physicians reported that at least 10% of their patients had self‐discontinued or reduced their immunosuppressive medication to mitigate the risk of COVID‐19 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also relates to the changes in treatment linked to the pandemic. A recent study performed among allergists, for example, reported that one third of participating physicians stopped systemic steroid treatment in their patients with asthma 35 . Another study performed among rheumatologists found that one third of participating physicians reported that at least 10% of their patients had self‐discontinued or reduced their immunosuppressive medication to mitigate the risk of COVID‐19 36 …”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed among allergists, for example, reported that one third of participating physicians stopped systemic steroid treatment in their patients with asthma. 35 and even higher rates in COVID-19 patients, linked to social isolation, the psychological impact of a novel severe and potentially fatal illness, concerns about infecting others, and stigma. 41 Stress leads to increased levels of neuropeptides such as substance P, which activates mast cells via the MRGPRX2.…”
Section: Discussionmentioning
confidence: 99%
“…During the COVID-19 pandemic, skin tests, blood tests, and OFCs were discontinued in some allergy clinics (7). In our clinic, the majority of patients had a scheduled OFC, mostly with cow's milk and hen's egg.…”
Section: Discussionmentioning
confidence: 98%
“…However, the ingestion of food allergenic products for OIT poses the risk of an adverse reaction [6]. Ozturk et al reported that only 21% of the respondents were continuing subcutaneous immunotherapy as usual during the COVID-19 pandemic [18]. Krishna et al reported that there was a highly significant decrease in subcutaneous immunotherapy up dosing and maintenance during the pandemic [19].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between the COVID-19 pandemic and FA treatments has been explored previously [10][11][12][13][14][15][16][17][18], although these reports were review articles (not surveys) [11][12][13][14][15][16][17] or small-scale surveys that included patients and their parents [10,18,19]. However, no large-scale study comprising more than 1000 subjects has evaluated the relationship between the COVID-19 pandemic and FA treatment.…”
Section: Introductionmentioning
confidence: 99%